A statistical analysis of Pc1–2 waves at a near-cusp station in Antarctica - M. Regi; M. Marzocchetti; P. Francia; M. De Lauretis (Earth, Planets and Space, 2017)
Abstract A statistical study of Pc1–2 waves at southern polar latitudes is presented. Ultra-low frequency geomagnetic field measurements collected at the Italian station Mario Zucchelli (Terra Nova Bay, Antarctica, altitude-adjusted corrected geomagnetic latitude 80°S, MLT = UT − 8) from 2003 to 2010 corresponding with the declining phase of solar cycle 23 and the onset of the solar cycle 24 are used. The long data series allows us to analyze the solar cycle, seasonal and magnetic local time dependence and investigate the possible generation processes related to the solar wind–magnetosphere interaction. We found that during the day, Pc1–2 waves occur around local magnetic noon and midnight. Polarized waves show an almost linear polarization, suggesting a wave propagation along a meridional ionospheric waveguide, from the injection region up to the latitude of Terra Nova Bay. The origin of the waves appears to be due to substorm/stormrelated instabilities and, in the dayside, to solar wind compressions of the magnetopause. Based on these results, we propose a simple model to estimate Pc1–2 power variations depending on geomagnetic activity and solar wind density.